Synthesis of hierarchical 5A zeolites to improve the separation efficiency of n-paraffins. Issue 5 (July 2019) - Liu, Jichang; Yang, Xuemei; Wang, Cheng; Ye, Lei; Sun, Hui
The diffusion coefficient of C3–C8 normal paraffins in 5A zeolite channels from the simulation ranged from 4.22 × 10 −10 cm 2 /s to 4.68 × 10 −14 cm 2 /s, indicating a slow mass transfer process. In addition, the diffusion rate becomes apparently slower with the increasing carbon numbers of the examined paraffins. In order to improve the adsorption separation efficiency of for n-paraffins, 5A zeolites with mesoporous structures were synthesized by hydrothermal method with the dimethyl octadecyl [3-(trimethoxysilyl)propyl] ammonium chloride as the template agent. Porosity and pore size distribution analysis demonstrated that micropores with the diameter of 0.5 nm were connected with 7–13 nm mesopores in the synthesized samples. The formation of hierarchical pore structure and change of surface morphology of zeolite particles could be controlled by the concentration of [3-(trimethoxysilyl)propyl] ammonium chloride used in the synthesis. The normal paraffin/cyclohexane solutions were used to investigate the adsorption kinetics of pentane, hexane, and heptane on the synthesized 5A zeolites. When the [3-(trimethoxysilyl)propyl] ammonium chloride concentration is 0.01%, the liquid phase diffusion coefficients of n-paraffins in the hierarchical 5A zeolite are 4–48 times larger than those in the microporous 5A zeolite. Our work demonstrates that the diffusion behavior and adsorption kinetics could be greatly improved by introducing mesoporosity into the pore structure of 5A zeolites.